6(2x-5)- (5x+7)=12x - 30 -5x -7=7x - 37
2,3(a+2) - 5(a-1,6)=2,3a +4,6 -5a +8= - 2,7a +12,6
- 2,7a+12,6= -2,7*( -3,4) + 12,6=9,18+ 12,6=21,78
1) 6(2x-5)-(5x+7)=12x-30-5x-7=12x-5x+(-30-7)=7x-37
2) 2,3(a+2)-5(a-1,6) считаем:
3) 2,3a+4,6-5a+8=2,3a-5a+4,6+8=-2,7a+12,6
если a=-3,4 то:
-2,7•(-3,4)=9,18. 9,18+12,6=21,78
Пошаговое объяснение:
Надеюсь, что
6(2x-5)- (5x+7)=12x - 30 -5x -7=7x - 37
2,3(a+2) - 5(a-1,6)=2,3a +4,6 -5a +8= - 2,7a +12,6
- 2,7a+12,6= -2,7*( -3,4) + 12,6=9,18+ 12,6=21,78
1) 6(2x-5)-(5x+7)=12x-30-5x-7=12x-5x+(-30-7)=7x-37
2) 2,3(a+2)-5(a-1,6) считаем:
3) 2,3a+4,6-5a+8=2,3a-5a+4,6+8=-2,7a+12,6
если a=-3,4 то:
-2,7•(-3,4)=9,18. 9,18+12,6=21,78
Пошаговое объяснение:
Надеюсь, что